Kontinuitas Budaya Mengemis Pada Transformasi Kampung Barak ke Kampung Baru - Nyimas Zahratul Azizah; Marshanda Sephira Harpy; Sunkina Niswatin (Pusat Riset dan Inovasi Nasional, 2023)
The phenomenon of begging, which emphasizes the hope of other people's compassion by selling the image of 'poverty', has become a sustainable social ecosystem that is unbroken from generation to generation because it has become a separate 'lifestyle' which is then interpreted by the perpetrators as part of a